Risk attitude and capital market participation: Is there a gender investment gap in Germany? - Jan-Christian Fey; Oliver Lerbs; Carolin Schmidt; Martin Weber (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Do women invest differently than men? We contribute to the answer of this question by analysing the Panel on Household Finances (PHF) of the German Bundesbank. This representative panel collects a wide variety of behavioural and financial variables in the area of household finance. We find that participation in risky assets is generally lower among women than among men. Once risk attitude is controlled for, this effect shrinks to only 2.6 percent. We find no difference when single women are compared to single men - even irrespective of other demographic variables. The raw gap in capital market participation is mainly explained by different risk attitudes and monetary endowments, but women would participate even less in the capital market if they reacted as sensitively to risk aversion as their male counterparts. Lastly, given participation in the market, we find that both genders hold comparable portions of risky assets in their portfolios. Within their risky assets, men invest more in certificates and listed shares whereas women invest more in funds.
Keywords: G11; 330; Capital market participation; gender; risk attitude; risky assets